Motion Control in Virtual Reality Based Teleoperation System - Abut, Tayfun; Soyguder, Servet (Ieee, 2015)
Teleoperation is a robot technology that allows people to prepare and develop the ability to tasks in unknown environments. Virtual reality is defined as a dynamic combination of technology which is a simulation environment created by a computer to obtain the natural interaction. Teleoperation of virtual and real-time robots is one of the objectives of this study. In this study, motion control was carried out using virtual reality in robotic teleoperation system. Besides, motion equations of virtual and real robot were obtained mid PID and feed-forward calculated torque control method were used to robot control. As a result, the target virtual environment created and one-way motion control was carried out with teleoperation. Applications in virtual and real environments were investigated with results.
Sanal Gerçeklik TabanllTeleoperasyon Sisteminde Hareket Kontrolü
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Teleoperation; Calculated Torque; PID; Virtual Robot; Realtime Robot